A scenario of pulsed ecrh wall conditioning in hydrogen for the Wendelstein 7-X helias - Moiseenko, V.E.; Beletskii, A.A.; Shapoval, A.M.; Wauters, T.; Goriaev, A.; Brunner, K.J.; Buttenschön, B.; Drewelow, P.; Winters, V.; Brakel, R.; Dinklage, A.; Brezinsek, S.; et al. (Вопросы атомной науки и техники, 2019)
A new wall conditioning scenario in hydrogen atmosphere for the Wendelstein 7-X stellarator-helias (W7-X) has been proposed and tested in part. Feasibility of the proposed scenario has been demonstrated on W7-X at OP1.2b experimental campaign during investigation of a chain of ultra-short pulsed electron cyclotron resonance heating plasma discharges.